The principle of mutual recognition in EU law - Janssens, Christine (Oxford : Oxford University Press, 2014)
Examining the principle of mutual recognition in the EU legal order, this volume asks whether the principle as developed in the internal market can and should be applied in judicial cooperation in criminal matters in the area of freedom, security and justice.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Recognition (International law); Criminal justice, Administration of -- European Union countries; Commercial Law -- European Union countries